Answer :

By splitting the middle term

2x^{2} + 7x/2 + 3/4 = 0

8x^{2} + 14x + 3 = 0

8x^{2} + (12x + 2x) + 3 = 0

8x^{2} + 12x + 2x + 3 = 0

4x (2x + 3) + (2x + 3) = 0

(2x + 3)(4x + 1) = 0

⇒ x = - 3/2, - 1/4

__Verification:__

Sum of the zeroes = - (coefficient of x) ÷ coefficient of x^{2}

α + β = - b/a

(- 3/2) + (- 1/4) = - (7)/4

= - 7/4 = - 7/4

Product of the zeroes = constant term ÷ coefficient of x^{2}

α β = c/a

(- 3/2)(- 1/4) =

3/8 = 3/8

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

<span lang="EN-USKC Sinha - Mathematics

<span lang="EN-USKC Sinha - Mathematics

<span lang="EN-USKC Sinha - Mathematics

Find the quadratiKC Sinha - Mathematics

Find a quadratic KC Sinha - Mathematics

If the product ofKC Sinha - Mathematics